The Application of Contemporary Business and Its Problems in Kelurahan Benda Baru Case Study of Small Traders - Dewi , Ririn Sari; Mu’arifin , Hidayatul (AGUSPATI Research Institute, 2021)
: The objectives of this study are 1) to determine the application of business contemporary in small traders in the sub-district of Benda baru pamulang, 2) to find out the problem with small traders in the village new thing pamulang. Methods of data analysis in this study using descriptive analysis and domain analysis. Research results 1) Business application these contemporary traders actually want to run it with new renewal by following the times, as in promote, market products, bookkeeping reports in a clear and appropriate manner with umkm report recording which is simple but still readable by report reader. 2) and the problems that have occurred so far still can be overcome by traders with the current situation and conditions.